MOTHER’S KNOWLEDGE REGARDING ORAL HEALTH PRACTICES AND RISK FACTORS WITH RESPECT TO THEIR CHILDREN IN THE TWIN CITIES OF PAKISTAN - Laila Mustafa (Army Medical College Rawalpindi, 2021)
Objective: To analyze the way mothers perceive oral health in their children, the importance of oral health amongst children, so that preventive advice and regime can be tailored accordingly and reinforced during the pandemic.